Pengaruh Semangat Kerja Dan Penghargaan Terhadap Kinerja Karyawan Di Bagian Pediatric Insentive Care Unit Pada Rumah Sakit Umum Kota Tangerang Selatan - Rehyan Septiawan Safikri; Jublina Oktora (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - The purpose of this study was to determine the effect of work spirit and appreciation on employee performance in a general hospital in the pediatric incentive care (PICU) section of South Tangerang. both partially and simultaneously. The method used in this study is a quantitative method. The sampling technique used is saturated sampling, which uses a sample of 50 respondents. The data analysis technique used is statistical analysis with validity test, reliability test, classical assumption test, simple linear test, multiple linear regression test, coefficient of determination, hypothesis t test and hypothesis f test. The results of the study of work spirit and appreciation on employee performance in a general hospital in the pediatric incentive care (PICU) section of South Tangerang. Shown by the multiple linear regression equation Y = 14.218 + 0.470 X1 + 0.179 X2. This is evidenced by the results of the simultaneous hypothesis test obtained the value of f count> f table (12.968> 3.19) and reinforced by a significance value <0.05 (0.000 <0.05). The results of the coefficient determination test of the work spirit (X1) and reward (X2) variables have an influence of 35.6% on employee performance at the general hospital in the pediatric incentive care (PICU) section of South Tangerang. Thus, H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between work spirit (X1) and reward (X2) on employee performance (Y).